Effects of hydrolyzed collagen supplementation for Skin Anti-Aging - Gliwa, Anna; Kurowski, Marek; Kuczapska, Karolina; Ryglewicz, Monika; Fabian, Dariusz; Leszczynska-Knaga, Elbieta; Jakubczyk, Natalia; Rutkowska-Kawalec, Weronika; Moczydłowski , Paweł; Michhalczuk, Karolina (Quality in Sport, 2025)
In an era of an aging population with the rise of social media, both men and women are paying more and more attention to the healthy appearance of their skin and overall health. Collagen is an essential component of the structure of the skin.With age, the amount of collagen in the skin decreases, there is a loss of elasticity as a result,wrinkles form and the appearance of the skin deteriorates. On the market there are more and more preparations both in the form of creams and means for oral application.One of the most popular dietary supplements that affect the quality of the skin and with tested bioavailability is hydrolyzed collagen . One can find many studies showing the positive effects of collagen supplementation on improving the quality and alleviating the visible signs of skin aging. In this review paper, we aim to evaluate the current state of knowledge of the effectiveness of hydrolyzed collagen supplementation on skin quality status. In order to investigate the efficacy and effects of hydrolyzed collagen for the skin, we need both preclinical studies, availability assessments and controlled clinical trials on a wide range of patients. Overall, it can be concluded that as little as 12 weeks of hydrolyzed fish collagen supplementation improves the quality and appearance of skin in the aging population.Importantly, HC-containing formulations were found to be safe and well-tolerated. However, further large-scale randomized controlled studies taking into account factors such as excipients in the supplements, age range and general lifestyle of the subjects are needed to confirm these results.